The Protective Effect of Magnesium Lithospermate B on Hepatic Ischemia/Reperfusion via Inhibiting the Jak2/Stat3 Signaling Pathway - Zhang, Ning; Han, Li; Xue, Yaru; Deng, Qiangqiang; Wu, Zhitao; Peng, Huige; Zhang, Yiting; Xuan, Lijiang; Pan, Guoyu; Fu, Qiang (Frontiers in Pharmacology, 2019)
Acute inflammation is an important component of the pathogenesis of hepatic ischaemia-reperfusion injury (HIRI). Magnesium lithospermate B (MLB) has strong neuroprotective and cardioprotective effects. The purpose of this study was to determine whether MLB had underlying protective effects against hepatic I/R injury and to reveal the potential mechanisms related to the hepatoprotective effects. In this study, we first examined the protective effect of MLB on HIRI in mice that underwent 1 h ischaemia followed by 6 h reperfusion. MLB pretreatment recovered the abnormal liver function and hepatocyte damage induced by I/R injury. We found that serum inflammatory cytokines, including IL-6, IL-1β and TNF-α, were significantly decreased by MLB during hepatic ischaemia/reperfusion (I/R) injury, suggesting that MLB may alleviate hepatic I/R injury via inhibiting inflammatory signalling pathways. Second, we investigated the protein expression of p-Jak2/Jak2 and p-Stat3/Stat3 using western blotting and found that MLB could significantly inhibit the activation of the Jak2/Stat3 signalling pathway, which was further verified by AG490 in mouse model. Finally, the effect of MLB on the Jak2/Stat3 pathway was further assessed in an in vitro model of RAW 264.7 cells. 1 µg/mL LPS induced the secretion of inflammatory mediators, including IL-6, TNF-α, and activation of the Jak2/Stat3 signalling pathway. MLB significantly inhibited the abnormal secretion of inflammatory factors and the activation of the Jak2/Stat3 signalling pathway in RAW264.7 cells. In conclusion, MLB was found for the first time to reduce inflammation induced by hepatic I/R via suppressing the Jak2/Stat3 pathway.